2019
DOI: 10.6061/clinics/2019/e1205
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Parameters of Gonadotropin-Releasing Hormone Analog Treatment Effectiveness in Children with Precocious Puberty

Abstract: OBJECTIVE:There are no doubts about the clinical benefits of treatment with GnRH analogs for patients diagnosed with central precocious puberty (CPP). However, laboratory monitoring of CPP is still a matter of considerable controversy in the literature. Therefore, the main objective of this study was to evaluate the cut-off values of stimulated LH that determine gonadotrophic suppression.METHODS:Twenty-four girls, on treatment with leuprorelin acetate (LA) at 3.75 mg IM every 28 days, were studied. The clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Such differences indicate the relevance of defining cutoff values according to the laboratory dosage method. Furthermore, most of the children had an LH peak at 60 min as suggested by Fujita et al [31], exempting the child from prolonged waiting and stress.…”
Section: Discussionmentioning
confidence: 91%
“…Such differences indicate the relevance of defining cutoff values according to the laboratory dosage method. Furthermore, most of the children had an LH peak at 60 min as suggested by Fujita et al [31], exempting the child from prolonged waiting and stress.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, the GnRH stimulation test continues to be the gold standard for discriminating IPT vs CPP in girls with premature thelarche [9][10][11][12][13]. Due to frequent unavailability of intravenous GnRH in many countries, stimulation testing with a widely available GnRH analog such as triptorelin, shown to induce comparable peaks of LH secretion, has been proposed as an alternative test for diagnosing CPP [3,11,12,[16][17][18][19][20]. In the present study, the potency of triptorelin to stimulate LH secretion has been confirmed by a significant strong correlation of peak LH responses after triptorelin injection compared to peak GnRH-stimulated LH concentrations (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, we must always have in mind that not everyone in the world has access to the same level of medical care, including the medications available for both diagnostic and therapeutic purposes. That is exactly the case with the intravenous GnRH preparation that is often unavailable in countries such as India, Brazil, Thailand, or Serbia [11,12,[16][17][18][19]. Also, with the widespread drug shortages seen during the current COVID-19 crisis and the global disruption of supply chains, the availability of the intravenous GnRH preparation may become affected even in wealthier countries worldwide [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gonadotropin-dependent precocious puberty, or central precocious puberty (CPP), is caused by premature activation of the HPG axis and can be treated with GnRH agonists. Patient history, physical examination, basal gonadotropin levels, and laboratory tests can be used to diagnose CPP [ 4 , 5 ] The GnRH stimulation test is considered the gold standard for detecting activation of the HPG axis [ 6 , 7 ]. CPP is diagnosed when bone age is more than 1 year higher than chronological age and when the peak luteinizing hormone (LH) level is above 5 mIU/mL during the GnRH stimulation test.…”
Section: Introductionmentioning
confidence: 99%